Potential pathogenic fungi assessment through molecular biology in cork industry - Viegas, Carla (2016)
Portugal has been the world leader in the cork sectr in terms of exports, employing ten thousands of workers. In this working activity, the permanent contact with cork may lead to the exposure to fungi raising concerns as occupational hazards in cork industry. A study was developed aiming at assessing fungal contamination due to Aspergillus fumigatus complex and Penicillium glabrum complex by molecular methods in three cork industries in the outskirt of Lisbon city. The chosen fungal species are the ones most frequently associated with respiratory problems in workers from these industries.